Aligning value propositions in supply chains. - Martinez, Veronica; Bititci, Umit S. (Inderscience, 2006)
Despite the plethora of studies on value that have been undertaken to date, organisations still fail in identifying their value offers, particularly in aligning their resources and capabilities towards their value creation processes in their supply chains. This research proposes a new framework on value creation: 'the value matrix'. The value matrix through its six value propositions provides a comprehensive framework to understand how different organisations within a supply chain create value. It explores value creation from both the organisational and customer perspectives. A constructive research approach through an in-depth case study on the fashion industry demonstrates that 1) the value propositions of key members of the supply chain should be aligned to enhance the value proposition of the entire supply chain. 2) Other members that are not strategic members of the supply chain can have different value propositions. This paper finishes with describing an agenda for further research and an agenda for changing how we design and operate supply chains.
Keywords: Materials and Manufacturing; Operational Management; Marketing and Services